Use of four asymmetric marks to orient the donor graft during Descemet's membrane endothelial keratoplasty. Issue 1 (4th August 2017) - Matsuzawa, Akiko; Hayashi, Takahiko; Oyakawa, Itaru; Yuda, Kentaro; Shimizu, Toshiki; Mizuki, Nobuhisa; Yamada, Norihiro; Kato, Naoko
Abstract : Introduction: Maintaining the correct orientation of the donor graft is important during Descemet's membrane endothelial keratoplasty (DMEK). We describe a new method of marking the donor graft prior to DMEK. Methods: Twelve eyes of 10 patients with bullous keratopathy who underwent DMEK were retrospectively analysed. Donor discs were created by stripping the endothelium–Descemet's membrane layer from corneoscleral buttons. Four semicircular marks, two 1.0 mm and two 1.5 mm in diameter, were created at the edge of the donor disc. The small and large marks were paired. Each donor graft was inserted into the anterior chamber, unfolded and attached to the posterior corneal stroma with an air bubble. Results: The inserted grafts were all appropriately orientated when attached to the back surfaces of the corneas. The two pairs of asymmetric marks afforded valuable guidance. Even when the graft was partially folded or decentred, and one pair of marks was obscured, the other pair was always visible to indicate graft orientation. Best spectacle-corrected visual acuity improved significantly in all patients (p<0.001). Compared with the preoperative endothelial cell density of the donor graft, that of the corneal endothelium had decreased 44.0%±10.0% by 6 months after surgery. Conclusions: Two pairs of asymmetrical semicircular marks placed on the edge of the donor graft allowed appropriate graft orientation during DMEK.